1995
DOI: 10.1002/marc.1995.030160409
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of metal‐complexing latices via polymerization in microemulsion

Abstract: Microlatex dispersions with ca. 120 m2 bipyridine-functionalized surface per g polymer were synthesized via copolymerization in microemulsion using two new cornonomers containing bipyridine groups. The resulting polymer particles were used for binding diverse metal ions in water as well as in organic solvents. Binding of the ions usually occurs intramolecularly. The colloidal characteristics of the dispersions are preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
3

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 17 publications
0
20
1
3
Order By: Relevance
“…Microemulsion polymerization yields stable latexes in the nanosize range (a 50 nm) that find applications in drug delivery, microencapsulation and biomedical diagnosis [156][157][158]. Most of these applications require highly functionalized particles, which have been prepared by using a second monomer bearing the desired functionality [159]. Larpent et al [160,161] reported on the use of polymerizable cosurfactants to produce highly functionalized nanoparticles.…”
Section: Microemulsion Polymerizationmentioning
confidence: 99%
“…Microemulsion polymerization yields stable latexes in the nanosize range (a 50 nm) that find applications in drug delivery, microencapsulation and biomedical diagnosis [156][157][158]. Most of these applications require highly functionalized particles, which have been prepared by using a second monomer bearing the desired functionality [159]. Larpent et al [160,161] reported on the use of polymerizable cosurfactants to produce highly functionalized nanoparticles.…”
Section: Microemulsion Polymerizationmentioning
confidence: 99%
“…Methacrylate-functionalized bipyridine ligands for the preparation of metal-complexing microlatex dispersions. [91] A system completely different to those shown above was presented by Lindsell et al in 1999, [92] in which they investigated polydiacetylenes with bipyridine ligands in the side chain as systems with nonlinear optical properties ( Figure 20). Figure 20.…”
Section: Polymers With Bipyridine Units In the Side Chainmentioning
confidence: 99%
“…W publikacjach [23][24][25][26] opisano wykorzystanie du-¿ej powierzchni w³aoeciwej nanolateksów do ich funkcjonalizowania odpowiednimi reagentami, np. kopolimerami styrenu, z nastêpuj¹cymi reaktywnymi komonomerami:…”
Section: Polimeryzacja I Kopolimeryzacjaunclassified